ALIH KODE DAN CAMPUR KODE DALAM NOVEL KIAI IBRAHIM DAN KERUKUNAN UMAT BERAGAMA KARYA IWAN MUCIPTO MOELIONO - Sabri Koebanu (PIKTORIAL : Journal of Humanities, 2019)
The purpose of this study is to describe the form and function of the use of code switching and code mixing contained in the conversations of novels Kiai Ibrahim and the Religious Harmony of Work by Iwan Mucipto Moeliono. The method used in this research is qualitative method. The results and discussion of this study were found in the form of code switching in three languages, namely: English, Arabic, and Javanese, while mixed code forms occur in five languages, namely: English, Arabic, Javanese, Sundanese, Balinese language.